ANALISA KINERJA PERUSAHAAN DENGAN MENGGUNAKAN METODE BALANCED SCORECARD ( Studi Kasus di PT. X CabangTabanan ) - Kiki Darini, Luh Putu Sukma; Mahatma Tuningrat, Ida Ayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember)
The aim of the research was to find out the performance of PT. X Tabanan. PT.X manages a fast food restaurant. Working system of this company is a franchise that performance in every branch of the company is not necessarily the same from one to the other, therefore necessary to analysis the performance of the company as a reference from the company to determine the elements that need to be improved. In this study, using a balanced scorecard method in measuring the performance of companies, in four perspectives namely, (1) the financial perspectives into a starting measuring the ratio of liquidity, solvency ratios, and profitability ratios, (2) customer perspective into starting measuring namely customer satisfaction and market segments, (3) business processes and internal perspective that became starting measuring that degree of innovation companies (Network Growth Ratio) and service operation Process (Administrative Ratio to Total Revenue) and (4) learning and growth perspective are cornerstones measuring the performance level of employees and the level of employee training. The results of that this study indicate that the company's performanceis quite goodbased on the calculationof the debt ratio, return on equity, market segments, the level of corporate innovation, processservice operationsand employee performance. Other results show that the performance included in the category of current ratios well as customer satisfaction, and employee training. The performance of the company that demonstrate less that the company's ability to generate profitability that the profitability of the consumer, the profit on sales, return on investment, and debt to equity ratio (debt with the ability to balance the total assets).
Keywords: 73,